Acyclovir-resistant herpes simplex virus 1 infection early after allogeneic hematopoietic stem cell transplantation with T-cell depletion. Issue 7 (July 2017) - Akahoshi, Yu; Kanda, Junya; Ohno, Ayumu; Komiya, Yusuke; Gomyo, Ayumi; Hayakawa, Jin; Harada, Naonori; Kameda, Kazuaki; Ugai, Tomotaka; Wada, Hidenori; Ishihara, Yuko; Kawamura, Koji; et al.
Abstract: We previously reported that oral low-dose acyclovir (200 mg/day) for the prevention of herpes simplex virus (HSV) infections after allogenic hematopoietic stem cell transplantation (HSCT) is effective without the emergence of acyclovir-resistant HSV infections. However, HSV infections are of significant concern because the number of allogeneic HSCT with T-cell depletion, which is a risk factor of the emergence of drug-resistant HSV infections, has been increasing. We experienced a 25-year-old female who received allogenic HSCT from an unrelated donor with 1-antigen mismatch using anti-thymocyte globulin. Despite acyclovir prophylaxis (200 mg/day), she developed the right palatal ulcer that was positive for HSV-1 specific antigen by fluorescent antibody on day 20 and developed new hypoglossal and tongue ulcers on day 33. Replacement of acyclovir with foscarnet improved her ulcers. We isolated 2 acyclovir-resistant and foscarnet-sensitive strains from the right palatal and hypoglossal ulcers, which had the same frame shift mutation in the thymidine kinase genes. The rate of proliferation of the isolate from the hypoglossal ulcer was faster than that from the right palatal ulcer in the plaque reduction assay. HSV strains that acquired acyclovir-resistant mutations at the right palatal ulcer with larger plaque might spread to the hypoglossal ulcer as the secondary site of infection because of better growth property. Second-line antiviral agents should be considered when we suspect treatment failure of HSV infection, especially in HSCT with T-cell depletion. Further studies are required whether low-dose acyclovir prophylaxis leads to the emergence of virological resistance.